(untitled) (Journal of EAHIL, 2024)
Dear all, for this issue’s “Publications and new products” column I’ve searched the web and selected news and articles regarding several current topics I hope would be of your interest. Among other news I’ve found on the web I would like to highlight some recent initiatives related to the switch towards prioritizing research quality over quantitative indicators when assessing research results.